(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Global Solid Waste Management (SWM) has become a severe challenge as a result of modern lifestyles that place a high priority on consumption and disposal. Pressure on our planet’s land space exacerbates the issue. Waste results in a significant waste of resources, including materials and energy. In fact, the amount of garbage generated might be seen as a measure of society’s materialism. The women were the backbone of the program. Their involvement in the program was necessary as they were the one who were responsible for daily segregation of the waste. Several methods were used to collect the data needed for this descriptive research. In order to comprehend a research technique, a descriptive and experimental design entails the process of gathering, evaluating, and "combining" either qualitative and quantitative information and methodologies. Findings showed that model was constructed and implemented in the urban societies. In total there were 130 houses under the implementation of the model. Women are the backbone of the society, as they played a major role in the implementation of this model. The senior citizens, women and children in the respective societies played an important role in the implementation of the model. As a result, the issue of SWM will be reduced to 70% when the Community based Model is used properly.